Genesis of the Zhijiadi Ag-Pb-Zn Deposit, Central North China Craton: Constraints from Fluid Inclusions and Stable Isotope Data - Tao Liu; Suo-Fei Xiong; Shao-Yong Jiang; Hua-Liang Li; Qi-Zhi Chen; Hai Jiang (Geofluids)
The Zhijiadi Ag-Pb-Zn deposit is located in the central North China Craton. Fluid inclusions (FIs) studies indicate three types of FIs, including aqueous, aqueous-carbonic, and daughter mineral-bearing multiphase inclusions. The daughter minerals in FIs are mainly composed of marcasite, chalcopyrite, calcite, and dolomite. Microthermometric data show that the homogenization temperature and salinity of FIs decrease gradually from early to late stages. Homogenization temperatures from early to main to late stages span from 244 to 334°C, from 164 to 298°C, and from 111 to 174°C, respectively, while their salinities are 4.0–9.9 wt.% NaCl equiv., 0.5–12.7 wt.% NaCl equiv., and 0.2–8.8 wt.% NaCl equiv., respectively. Trapping pressures drop from 203–299 MPa (the early stage) to 32–158 MPa (the main stage). The dropping of pressure and temperature and mixing and/or dilution of ore-forming fluids result in the formation of ore deposit. Combined with C-O-S-Pb isotopic compositions, the initial ore-forming fluids and materials were likely derived from a magmatic system. As a whole, we proposed that this deposit belongs to medium-low temperature hydrothermal deposit related to volcanic and subvolcanic magmatism strictly controlled by the fault zones.